Orodispersible polymer films with the poorly water-soluble drug, olanzapine: Hot-melt pneumatic extrusion for single-process 3D printing - Cho, Hui Won; Baek, Seung Hoon; Lee, Beom Jin; Jin, Hyo Eon (Pharmaceutics, 2020)
Amorphous solid dispersions (ASDs) improve the oral delivery of poorly water-soluble drugs. ASDs of olanzapine (OLZ), which have a high melting point and low solubility, are performed using a complicated process. Three-dimensional (3D) printing based on hot-melt pneumatic extrusion (HMPE) is a simplified method for producing ASDs. Unlike general 3D printing, printlet extrusion is possible without the preparation of drug-loaded filaments. By heating powder blends, direct fused deposition modeling (FDM) printing through a nozzle is possible, and this step produces ASDs of drugs. In this study, we developed orodispersible films (ODFs) loaded with OLZ as a poorly water-soluble drug. Various ratios of film-forming polymers and plasticizers were investigated to enhance the printability and optimize the printing temperature. Scanning electron microscopy (SEM) showed the surface morphology of the film for the optimization of the polymer carrier ratios. Differential scanning calorimetry (DSC) was used to evaluate thermal properties. Powder X-ray diffraction (PXRD) confirmed the physical form of the drug during printing. The 3D printed ODF formulations successfully loaded ASDs of OLZ using HMPE. Our ODFs showed fast disintegration patterns within 22 s, and rapidly dissolved and reached up to 88% dissolution within 5 min in the dissolution test. ODFs fabricated using HMPE in a single process of 3D printing increased the dissolution rates of the poorly water-soluble drug, which could be a suitable formulation for fast drug absorption. Moreover, this new technology showed prompt fabrication feasibility of various formulations and ASD formation of poorly water-soluble drugs as a single process. The immediate dissolution within a few minutes of ODFs with OLZ, an atypical antipsychotic, is preferred for drug compliance and administration convenience.
Keywords: Disintegration; Dissolution; Hot-melt extrusion; Orodispersible film; Poorly water-soluble drugs; Three-dimensional printing technology